Evaluation of factors that motivate participants to consent for non-therapeutic trials in India. Issue 6 (8th March 2013) - Doshi, Maulik Sumantbhai; Kulkarni, Shaunak P; Ghia, Canna J; Gogtay, Nithya J; Thatte, Urmila Mukund
Abstract : Background and rationale: Several factors that motivate individuals to participate in non-therapeutic studies have been identified. This study was conducted as limited data is available regarding these motivations from developing countries. Methods: This was a single-centre study conducted over 4 months in which a questionnaire was administered to 102 healthy participants and 16 patient participants who had earlier taken part in non-therapeutic studies at our centre. Descriptive statistics and univariate analysis were used to analyse data. Results: The most common motivation among healthy participants was financial reward (65%) followed by altruism, free medical check up, curiosity and personal health benefit. Patient participants, however, most commonly said they consented to take part in the trial as they were 'invited to participate by the treating physician' (88%). In comparison with the patient participants, healthy participants were more likely to be satisfied with the financial reward (p=0.02), and recommend participation in studies to friends or relatives (p=0.0013). Conclusions: The most common motivating factor to participate in non-therapeutic studies appears to be different for healthy participants (financial reward) and patient participants (invitation to participate by the physician). Participants also felt that adequate information and care was given to them during the trial, and that they would participate in future clinical studies, and would also recommend such studies to their friends.